The provision of Primary Health Care in two rural districts of the Eastern Cape Province with particular reference to human resources and accessibility - M. Thipanyana; T.R. Mavundla (AOSIS, 1998)
The provision of Primary Health Care Services (PHC) is still a problem in developing countries like South Africa. In other countries, one finds enough human resources whilst in other countries there may be enough material resources. A both qualitative and quantitative research was conducted at Mqanduli and part of the Eastern Elliotdale districts in the Eastern Cape Province with the aim of investigating the provision of Primary health Care Services, reference was made to the availability of human resources and accessibility of PHC services.